Circular Object Sorting Machine with LabVIEW Software Control - Pratya Mongkolwai; Jetsdaporn Satansup; Teerasilapa Dumawipata; Teerapat Nakroungsri; Monthathip Laotuy; Worapong Tangsrirat (My University, 2024)
This article describes a project to construct a circular object-sorting machine through the application of image-processing techniques. For the acquisition, processing, and transmission of data, LabVIEW (Laboratory Virtual Instrument Engineering Workbench) software is utilized. The operation of the sorting device is controlled by an Arduino microcontroller board, which is the Arduino Mega 2560. The project aims to efficiently separate circular objects by extracting color information, size measurements, and quantity data through image processing. The experimental results successfully demonstrate the sorting of circular objects and display color values, size measurements, and the number of sorted objects on an efficient LCD screen. The integration of LabVIEW and Arduino provides an effective solution for circular object sorting, aligning with the theoretical principles presented in the project.
Keywords: Industrial Automation and Control Systems; Fault Detection and Control Systems